PJMHS 2022
DOI: 10.53350/pjmhs22163315
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes of Circumcisions among Children 0-4 years by using Gomco Versus Plastibell Techniques

Abstract: Objective: We aimed to compare the rate of complications of Gomco and Plastibell circumcision techniques ininfants. Study design:Prospective Randomized Clinical TrialStudy. Place and duration of study:Department of Pediatric Surgery, Sheikh Zayed Hospital, Rahim Yar Khanfor six months from August 2020 to July 2021. Patients and method: A total of 80 patients were enrolled in the study, equally divided into two groups. Group 1 included patients undergoing circumcision via the Gomco technique, while group 2 circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…10 Each technique has its own advantages and disadvantages, with bleeding considered the most common overall complications. 10 , 11 A number of studies were conducted to compare the outcomes between different methods of circumcision 8,12 showed that GOMCO procedure was associated with more bleeding while, on the other hand, the Plastibell procedure was associated with more redundant preputial skin.…”
Section: Discussionmentioning
confidence: 99%
“…10 Each technique has its own advantages and disadvantages, with bleeding considered the most common overall complications. 10 , 11 A number of studies were conducted to compare the outcomes between different methods of circumcision 8,12 showed that GOMCO procedure was associated with more bleeding while, on the other hand, the Plastibell procedure was associated with more redundant preputial skin.…”
Section: Discussionmentioning
confidence: 99%